FAKTOR-FAKTOR PENENTU TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA TENGAH TAHUN 2013-2015 - Agus Budi Prasetyo, 14.05.62.0024; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the effect of size of the local government, intergovernmental revenue, age of the of the local government, size legislative, number of population, original local government revenue and functional differentiation of the local government to disclosure of the Local Government Financial Report (LGFR) distric/city of central java province. The population of this research is Indonesiaâs local government distric/city of central java province with sample Local Government Financial Report (LGFR) during the years 2013 to 2015. Samples are included in the criteria of this study were 105 Local Government Financial Report (LGFR) using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis using SPSS 20. The results showed that the variables of size legislative and original local government revenue significant positive effect to disclosure of the level Local Government Financial Report (LGFR), while size of the local government, intergovernmental revenue, age of the of the local government, number of population and functional differentiation of the local government have no effect to disclosure of the level Local Government Financial Report (LGFR).Keywords: Size of The Local Government, Intergovernmental Revenue, Age of The of The Local Government, Size Legislative, Number of Population, Original Local Government Revenue and Functional Differentiation